On Being Ironic: Pragmatic and Mnemonic Implications - Kreuz, Roger J.; Long, Debra L.; Church, Mary B. (Metaphor and symbolic activity, 1991)
Two experiments investigated (a) subjects' intuitions about the communicative functions of irony and (b) how communicative functions affect recall. Previous research (Long, Kreuz, & Church, 1989) suggested that ironic statements allow speakers to fulfill communication goals that are difficult to convey literally. The present research extends these findings by identifying which communication goals (and other factors) influence recall. In Experiment 1, subjects read scenarios that concluded with ironic or literal statements and selected goals fulfilled by the statements from a checklist. The results indicated that ironic statements fulfill more communication goals than literal statements. In Experiment 2, subjects recalled these scenarios after a 24-hr delay. Presence of irony and fulfillment of pragmatically salient goals predicted recall in a series of multiple regression analyses.